The Distribution of Benthic Foraminifera in Indonesian Shallow Waters - Suhartati M. Natsir (Ikatan Ahli Geologi Indonesia, 2014)
Indonesia has diverse marine ecosystems, ranging from estuary, mangrove, seagrass beds, coral reefs, to deep sea, all suitable habitats for marine organisms. Many studies on the distribution of foraminifera in Indonesia waters have been conducted by the Research Center for Oceanography in Jakarta in recent years. Between 1994 and 2012 benthic foraminifera were recorded in environments ranging from estuary, mangrove, seagrass beds, coral reefs to deep sea. This study presents some of the results from several expeditions in shallow waters. Foraminifera were given special attention since there were relatively few records on the modern distribution of this group from Indonesia.Samples from estuaries contain higher numbers of agglutinated foraminifera in coarser sediments. Assemblages from near the river mouth of the Solo and Delta Porong Deltas of NE Java are dominated by Textularia spp., Haplophragmoides canariensis and Ammobaculites agglutinans. The waters of Handeuleum Islands off SW Java, with three types of ecosystems, are dominated by opportunistic benthic foraminifera, i.e. Ammonia beccarii. The most abundant benthic foraminifera are in fine sandy sediments collected adjacent to the mainland in areas characterized by coral reefs communities. Benthic foraminifera are less common in samples collected from seagrass beds with silty and muddy sediments. Coral reefs ecosystems studied at Jukung and Damar Besar Islands were dominated by symbiont-bearing foraminifera like Amphistegina, Calcarina, Heterostegina, Marginopora and Operculina.